Method for reducing sodium ions in cobaltosic oxide by ion exchange post-treatment method

Through the ion exchange post-treatment method, the ion exchange reaction is carried out using ammonium chloride aqueous solution or ammonia water to remove sodium ions in cobalt tetroxide, solving the problems of low efficiency and high cost in the existing technology, and achieving efficient and low-cost sodium ion removal , improves material performance and applicability.

CN119160947AActive Publication Date: 2024-12-20GEM JIANGSU COBALT IND CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411479763.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-20
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The prior art methods for reducing sodium ions in cobalt tetroxide are inefficient and costly, which are harmful to product quality and are difficult to effectively remove sodium ion impurities, affecting the electrochemical performance and structural integrity of the material.

Method used

By ion exchange post-treatment method, the ion exchange reaction is carried out by powder slurry, adding ammonium chloride aqueous solution or ammonia water, stirring, and then filtering and drying, controlling the solid-liquid ratio, stirring speed, temperature and concentration to achieve the removal of sodium ions. The exchange capacity of ammonium ions and sodium ions is gradually replaced and removed.

Benefits of technology

It achieves efficient and low-cost reduction of the content of sodium ions in cobalt tetroxide, improves the electrochemical performance and structural integrity of the material, is simple to operate, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160947A_ABST
    Figure CN119160947A_ABST
Patent Text Reader

Abstract

The invention discloses a method for reducing sodium ions in cobaltosic oxide through an ion exchange post-treatment method, and belongs to the technical field of cobaltosic oxide treatment. The method comprises the following steps: (1) pulpifying powder: mixing cobaltosic oxide powder and water to form a pulpified material; (2) adding a reagent: adding an ammonium chloride aqueous solution or ammonia water into the pulpified material to obtain a mixture; (3) ion exchange: carrying out an ion exchange reaction on the mixture under a stirring condition to obtain a crude product; and (4) purification: filtering the crude product to collect solid cobaltosic oxide, re-mixing the obtained filter cake with water, repeatedly filtering to remove residual ions on the solid surface, and drying to obtain the cobaltosic oxide. The method has the advantages of being high in efficiency, low in cost and small in damage to product quality, the method is easy to operate, the cost of used reagents is low, and industrial production is easy to achieve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cobalt tetroxide treatment, and in particular to a method for reducing sodium ions in cobalt tetroxide by an ion exchange post-treatment method. Background Art

[0002] The battery of 3C electronic products such as large-capacity mobile phones, laptops, digital cameras, etc. is its terminal application field. 3C electronic products are required to be light and compact, so the corresponding batteries must have high energy density. Lithium cobalt oxide is (LiCoO 2 ) Currently, the most important positive electrode material used in 3C electronic products, the energy density of lithium-ion batteries depends to a certain extent on the energy density of lithium cobalt oxide.

[0003] Cobalt tetraoxide (Co 3 O 4 ) is an important precursor for the preparation of lithium cobalt oxide positive electrode materials. In lithium-ion batteries, lithium cobalt oxide is widely used as a positive electrode material due to its high theoretical specific capacity and good electrochemical properties. The main role of cobalt tetroxide in the preparation process is to provide a cobalt source and to be converted into lithium cobalt oxide in the subsequent high-temperature calcination process. The particle size and morphology of cobalt tetroxide have an important influence on the performance of the final lithium cobalt oxide material. For example, by controlling the particle size distribution of cobalt tetroxide, the compaction density of lithium cobalt oxide can be increased, thereby increasing the volume energy density of the battery. In addition, the microstructure and purity of cobalt tetroxide will also affect the electrochemical properties of lithium cobalt oxide, including cycle stability and rate performance.

[0004] In the production process of cobalt tetroxide, there is often a certain amount of sodium ion impurities. The sodium ions may be due to the fact that the cobalt tetroxide and cobalt oxyhydroxide are too densely packed during the synthesis process, resulting in the sodium ions being wrapped inside the crystal. In addition, raw materials or reagents containing sodium may be used in the production process of cobalt tetroxide, which will also lead to the enrichment of sodium ions in the material. Even in the subsequent purification steps, sodium ions may remain in the material if not handled properly. The reason why sodium ion impurities are difficult to remove may be related to their distribution in the cobalt tetroxide crystal structure. In some cases, sodium ions may penetrate deep into the crystal and form a tight bond with cobalt ions, which makes it difficult to effectively remove them by simple washing or chemical treatment.

[0005] Residual sodium ions will have an adverse effect on the performance and application of cobalt tetroxide. The presence of sodium ions may affect the electrochemical properties of cobalt tetroxide, especially when used as a positive electrode material for lithium-ion batteries. Sodium ions may also replace lithium ions in the electrode material, thereby reducing the energy density and cycle stability of the battery. In addition, the presence of sodium ions may also affect the structural integrity and thermal stability of the material, thereby affecting the processing performance and final application of the material.

[0006] In order to reduce the content of sodium ions, a more sophisticated and specially designed purification method is needed. However, the commonly used methods for reducing sodium ions have problems such as low efficiency, high cost or certain damage to product quality. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a method for reducing sodium ions in cobalt tetroxide by an ion exchange post-treatment method with high efficiency, low cost and little damage to product quality is provided, comprising the following steps: (1) Powder slurry: Mix cobalt tetroxide powder and water to form a slurry; (2) Adding reagents: adding an aqueous solution of ammonium chloride or aqueous ammonia to the slurry to obtain a mixed material; (3) Ion exchange: The mixture undergoes ion exchange reaction under stirring conditions, and a crude product is obtained after completion; (4) Purification: Filter the crude product to collect solid cobalt tetroxide, remix the resulting filter cake with water, and filter repeatedly to remove residual ions on the solid surface. After drying, cobalt tetroxide is obtained.

[0008] In the process of mixing cobalt oxide powder and water to form slurry, the control of solid-liquid ratio is very important because it directly affects the rheology and stability of the slurry. If there is too much water, the slurry may be too fluid, resulting in a reduction in the shear force effect of the stirring paddle, which is not conducive to the kneading and stirring to play the role of kneading force to crush and agglomerate. On the contrary, if the cobalt oxide powder content is too high, the slurry may be too dense and difficult to stir evenly, affecting the homogeneity of the slurry. The appropriate solid-liquid ratio helps to maintain the stability of the slurry and prevent particles from reagglomerating.

[0009] Preferably, in step (1), the solid-to-liquid ratio of cobalt oxide powder to water is 1:20-30 g / g.

[0010] Preferably, in step (1), the mixing method is stirring, and the stirring speed is 300-500 rpm.

[0011] In the present invention, the degree of sodium ion removal can be flexibly controlled by adjusting the concentration of ammonia water or ammonium chloride aqueous solution and the reaction conditions. In order to ensure the high efficiency of the ion exchange reaction, it is necessary to control the reaction temperature and the reactant concentration within a suitable range. Appropriate temperature and concentration can ensure the stability of the ion exchange process, reduce reaction energy consumption, and improve efficiency. In industrial production, maintaining constant operating conditions can also ensure the consistency of product quality and reduce energy consumption. The rate of ion exchange reactions is affected by ion concentration. Generally speaking, the higher the ion concentration, the faster the rate of ion exchange reactions, because more ions in the solution increase the chance of collision, thereby speeding up the reaction process. However, an increase in ion concentration may also cause the ion exchange equilibrium to shift, affecting the final exchange efficiency and selectivity. Temperature has an important influence on both the rate and equilibrium position of ion exchange reactions.

[0012] Preferably, in step (2), the concentration of the aqueous ammonium chloride solution is 10-20 g / L; the concentration of the aqueous ammonia solution is 5 wt.%-25.0 wt.%.

[0013] Preferably, in step (2), the volume ratio of the aqueous ammonium chloride solution or aqueous ammonia to the slurry is 1:3-5.

[0014] Preferably, in step (3), the stirring speed is 300-500 rpm.

[0015] Increasing temperature usually accelerates the rate of ion exchange reactions because high temperature can provide more energy to the reaction system and increase the speed of molecular movement. Temperature can also change the selectivity of ion exchange, that is, the affinity for different ions, thereby improving separation efficiency and purity in some applications. However, excessive temperature increases may cause changes in the physical and chemical properties of ion exchange, thereby impairing its performance.

[0016] Preferably, in step (3), the temperature of the ion exchange reaction is 60-80° C., and the reaction time is 4-8 h.

[0017] The appropriate solid-liquid ratio can ensure that the filter cake is not too dense, so that a reasonable filtration channel can be maintained, allowing the filtrate to pass smoothly and multiple filtrations to proceed smoothly. If the solid-liquid ratio is too high, that is, the solid content in the filter cake is too high, the filter cake layer will become too dense, increase the filtration resistance, and thus reduce the filtration speed. In addition, controlling the appropriate solid-liquid ratio helps to form a loosely structured filter cake, which is very beneficial for the subsequent washing and drying steps. If the filter cake is too dense, it may cause uneven washing and drying, affecting the purity and yield of the final cobalt oxide.

[0018] Preferably, in step (4), the solid-liquid ratio of the mixture of filter cake and water is 1:40-100 g / g.

[0019] Preferably, in step (4), the filtering method is suction filtration; the suction filtration is repeated 1-5 times to remove the residual ions on the solid surface.

[0020] Ion exchange reaction is a process based on selective adsorption and release between ions. In this process, when a solution containing different ions passes through an ion exchange medium, the ions in the solution are adsorbed or released according to their different affinity with the selected ions. The present invention utilizes the difference in exchange capacity between ammonium ions and sodium ions, based on the selectivity of ion exchange, through the above-mentioned operating conditions and ion exchange medium, to effectively reduce the sodium ion content.

[0021] The sodium ions in cobalt oxide are difficult to remove by normal washing. These ions are formed by the complexation of cobalt ions and complexing agents. When they react with precipitants, they are adsorbed to the surface of the material grains. The adsorption capacity of these ions is relatively strong. Ammonium ions, which are the same cations as sodium ions, have a much stronger adsorption capacity to the negatively charged groups on the surface of the material than sodium ions. When ammonium ions are added, the sodium ions in cobalt oxide will be gradually replaced by ammonium ions and removed by washing, thereby achieving the purpose of reducing sodium ions.

[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention provides a method for reducing sodium ions in cobalt tetroxide by an ion exchange post-treatment method, which has the advantages of high efficiency, low cost and little damage to product quality. The method is simple to operate, uses low reagent cost and is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic flow chart of the method for reducing sodium ions in cobalt tetroxide by the ion exchange post-treatment method in Example 1. DETAILED DESCRIPTION

[0024] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0025] Example 1 A method for reducing sodium ions in cobalt tetraoxide by ion exchange post-treatment, such as Figure 1 As shown, the steps are as follows: (1) Powder slurry: Place cobalt tetroxide powder (black powder) and deionized water in a clean beaker at a solid-liquid ratio of 1:20 g / g, stir evenly at a stirring speed of 450 rpm to form a slurry; (2) Adding reagents: adding 10 g / L of ammonium chloride aqueous solution to the slurry, with the volume ratio of the ammonium chloride aqueous solution to the slurry being 1:3, to obtain a mixed material; (3) Ion exchange: The mixture was subjected to ion exchange reaction under stirring conditions of 400 rpm, the slurry temperature was maintained at 72 °C, and the ion exchange time was 5 h. After completion, a crude product was obtained; (4) Purification: Filter the crude product to collect solid cobalt tetroxide. Place the filter cake in a beaker and add deionized water again. The solid-liquid ratio is 1:40-1:100 g / g. After ultrasonic-assisted dispersion, continue to filter. Repeat this process three times to remove residual ions on the solid surface. After drying, cobalt tetroxide (black powder) is obtained.

[0026] Example 2 This embodiment is basically the same as Embodiment 1, except that the concentration of the sodium chloride aqueous solution used in this embodiment is 20 g / L.

[0027] Example 3 This embodiment is basically the same as Embodiment 1, except that the concentration of the sodium chloride aqueous solution used in this embodiment is 30 g / L.

[0028] Example 4 This embodiment is basically the same as Embodiment 1, except that the concentration of the sodium chloride aqueous solution used in this embodiment is 40 g / L.

[0029] Example 5 This example is basically the same as Example 1, except that the concentration of the sodium chloride aqueous solution used in this example is 50 g / L.

[0030] Example 6 This embodiment is basically the same as Embodiment 1, except that the reagent used in this embodiment is 5 wt.% ammonia water.

[0031] Example 7 This embodiment is basically the same as Embodiment 6, except that the concentration of ammonia water used in this embodiment is 10 wt.%.

[0032] Example 8 This embodiment is basically the same as Embodiment 6, except that the concentration of ammonia water used in this embodiment is 15 wt.%.

[0033] Example 9 This embodiment is basically the same as Embodiment 6, except that the concentration of ammonia water used in this embodiment is 20 wt.%.

[0034] Example 10 This embodiment is basically the same as Embodiment 6, except that the concentration of ammonia water used in this embodiment is 25 wt.%.

[0035] Comparative Example 1 This comparative example uses the treatment method without adding ammonia water or ammonium chloride aqueous solution as a comparison, and the steps are as follows: (1) Powder slurry: Place cobalt tetroxide powder and deionized water in a clean beaker at a solid-liquid ratio of 1:20 g / g, stir evenly at a stirring speed of 450 rpm to form a slurry; (2) Purification: Filter the slurry to collect solid cobalt tetroxide, place the filter cake in a beaker, add deionized water again, and the solid-liquid ratio is 1:40-1:100 g / g. After ultrasonic-assisted dispersion, continue to filter. Repeat this process three times to remove residual ions on the solid surface. After drying, cobalt tetroxide is obtained.

[0036] First, cobalt tetraoxide was digested with strong acid, and then the sodium ion content was tested by ICP. The sodium ion content in the product was tested under different concentrations of ammonium chloride aqueous solution and ammonia water, and when no ion exchange was performed, as shown in Table 1 and Table 2 respectively.

[0037] Table 1: Relationship between the sodium ion content in cobalt tetroxide and the concentration of ammonium chloride aqueous solution

[0038] Table 2: Relationship between the sodium ion content in cobalt tetroxide and the concentration of ammonia water

[0039] The increase in the concentration of ammonium chloride aqueous solution or ammonia water does not show a positive correlation with the degree of reduction in sodium ion content. After the concentration increases to a certain level, the effect of reducing the sodium ion content rebounds. Therefore, the degree of sodium ion removal can be flexibly controlled by adjusting the concentration of ammonia water or ammonium chloride aqueous solution and the reaction conditions.

[0040] The invention provides a method for reducing sodium ions in cobalt tetroxide by an ion exchange post-treatment method, which has the advantages of high efficiency, low cost and little damage to product quality. The method is simple to operate, uses low reagent costs and is easy to realize industrial production.

[0041] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for reducing sodium ions in cobalt tetroxide by ion exchange post-treatment, characterized in that: The steps include: (1) Powder slurry: Mix cobalt tetroxide powder and water to form a slurry; (2) Adding reagents: adding an aqueous solution of ammonium chloride or aqueous ammonia to the slurry to obtain a mixed material; (3) Ion exchange: The mixture undergoes ion exchange reaction under stirring conditions, and a crude product is obtained after completion; (4) Purification: Filter the crude product to collect solid cobalt tetroxide, remix the resulting filter cake with water, and filter repeatedly to remove residual ions on the solid surface. After drying, cobalt tetroxide is obtained.

2. The method for reducing sodium ions in cobalt tetroxide by ion exchange post-treatment according to claim 1, characterized in that: In the step (1), the solid-to-liquid ratio of cobalt oxide powder to water is 1:20-30 g / g.

3. The method for reducing sodium ions in cobalt tetroxide by ion exchange post-treatment according to claim 1, characterized in that: In the step (1), the mixing method is stirring, and the stirring speed is 300-500 rpm.

4. The method for reducing sodium ions in cobalt tetroxide by ion exchange post-treatment according to claim 1, characterized in that: In the step (2), the concentration of the aqueous ammonium chloride solution is 10-20 g / L; the concentration of the aqueous ammonia solution is 5 wt.%-25.0 wt.%.

5. The method for reducing sodium ions in cobalt tetroxide by ion exchange post-treatment according to claim 1, characterized in that: In the step (2), the volume ratio of the aqueous ammonium chloride solution or ammonia water to the slurry is 1:3-5.

6. The method for reducing sodium ions in cobalt tetroxide by ion exchange post-treatment according to claim 1, characterized in that: In the step (3), the stirring speed is 300-500 rpm.

7. The method for reducing sodium ions in cobalt tetroxide by ion exchange post-treatment according to claim 1, characterized in that: In the step (3), the temperature of the ion exchange reaction is 60-80°C and the reaction time is 4-8 hours.

8. The method for reducing sodium ions in cobalt tetroxide by ion exchange post-treatment according to claim 1, characterized in that: In the step (4), the solid-liquid ratio of the filter cake mixed with water is 1:40-100 g / g.

9. The method for reducing sodium ions in cobalt tetroxide by ion exchange post-treatment according to claim 1, characterized in that: In the step (4), the filtering method is suction filtration; the suction filtration is repeated 1-5 times to remove the residual ions on the solid surface.

Citation Information

Patent Citations

  • Method for removing impurity element Na and S in precursor cobalt salts of cobaltosic oxide

    CN101337696A

  • Technology for preparing cobaltosic oxide by cobalt-containing solution

    CN103318976A

  • Method for preparing small-particle size high-density spherical cobalt (II,III) oxide

    CN104134786A

  • Preparation method and device of low-sodium cobalt tetroxide

    CN108862405A

  • Production method of battery-grade cobalt oxide

    CN112408500A